2017
DOI: 10.1111/1744-9987.12530
|View full text |Cite
|
Sign up to set email alerts
|

Elevated High Sensitivity C‐Reactive Protein Increases the Risk of Microalbuminuria in Subjects With Cardiovascular Disease Risk Factors

Abstract: Microalbuminuria is an early biomarker of kidney injury, the aim of this study was to investigate the impact of high sensitivity C-reactive protein (hs-CRP) on microalbuminuria in adults with cardiovascular disease (CVD) risk factors. A total of 5667 subjects who voluntarily attended annual health screenings in the Third Xiangya Hospital of Central South University were included in the study. Logistic regression was used to determine the validity of hs-CRP to predict the presence of microalbuminuria. In the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Microalbuminuria was also more common in smokers with high hs-CRP than in smokers with normal hs-CRP. Similar finding was also found in obese subjects with high hs-CRP compared to non-obese subjects with normal hs-CRP (Yang et al, 2017). A research in Singapore showed that people with CRP levels of >3 mg/L were 1.6 times more likely to develop micro-and macroalbuminuria than people with CRP levels of <1 mg/L (odds ratio=1.60; 95% CI: 1.26-2.04; p=0.0001) (Sabanayagam et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Microalbuminuria was also more common in smokers with high hs-CRP than in smokers with normal hs-CRP. Similar finding was also found in obese subjects with high hs-CRP compared to non-obese subjects with normal hs-CRP (Yang et al, 2017). A research in Singapore showed that people with CRP levels of >3 mg/L were 1.6 times more likely to develop micro-and macroalbuminuria than people with CRP levels of <1 mg/L (odds ratio=1.60; 95% CI: 1.26-2.04; p=0.0001) (Sabanayagam et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, elevated CRP also promotes overproduction of pro-inflammatory cytokines, then leads to glomerular mesangial cell proliferation and increases in renal vascular permeability, eventually resulting in albuminuria. There is a close relationship between inflammation and activation of the renin-angiotensin system and oxidative stress, leading to glomerular hyperfiltration and albuminuria (Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, early intervention can help prevent kidney disease. 50,51 Also, the progression of diabetic nephropathy can be insidious and lead to major complications for obese individuals. 51 A study from Portugal by Lobato et al (2003) identified that patients with the presence of microalbuminuria at the early stage are more susceptible to developing nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Also, the progression of diabetic nephropathy can be insidious and lead to major complications for obese individuals. 51 A study from Portugal by Lobato et al (2003) identified that patients with the presence of microalbuminuria at the early stage are more susceptible to developing nephropathy. Therefore, they concluded that the measurement of microalbuminuria could be a prognostic indicator for renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al have shown that in patients with cardiovascular disease, elevated levels of high-sensitivity CRP increase the risk of developing microalbuminuria [ 26 ]. It cannot be excluded that we would observe a similar association with longer duration of obesity.…”
Section: Discussionmentioning
confidence: 99%